Anodic Zirconium Dioxide-Based Nanotubes For Photoreduction Of Hexavalent Chromium (Cr(Vi) - Bashirom, Nurulhuda (2019)
Contamination of water by harmful heavy metal ions like hexavalent chromium, Cr(VI) is one of the major global concerns. Exposure to Cr(VI) can cause severe health problems as Cr(VI) is carcinogen. Removal of Cr(VI) from point of wastewater discharged is therefore required. One of the method to remove Cr(VI) from industrial wastewater is by reducing Cr(VI) to less harmful Cr(III) on a suitable photocatalyst. ZrO2-based nanotubes were fabricated for Cr(VI) photoreduction: freestanding ZrO2 nanotubes (FSZNTs), mixed oxides t-ZrO2 + a-TiO2 + amorphous ZrTiO2 nanotubes and orthorhombic-ZrTiO4 + a-TiO2 nanotubes (ZTNTs), and mixed oxides m-ZrO2 + α-Fe2O3 + Fe3O4 nanotubes (ZFNTs) by anodization of Zr, Ti-40 wt.% Zr, and Fe-40 wt.% Zr foils respectively. Anodization was conducted in F- containing ethylene glycol electrolyte at varying anodization parameters i.e. NH4F concentration, K2CO3 or water volume, applied voltage, and anodization time. Length of FSZNTs increased from 5.6 to 12.5 μm with increasing anodization time but decreased at high NH4F, high K2CO3, and high applied voltage due to accelerated chemical dissolution at oxide|electrolyte interface. Whereas, the ZTNTs length increased up to 28.6 μm with increasing anodization time, applied voltage, and NH4F but decreased to 7.5 μm in 9 vol.% water due to excessive chemical dissolution at ZTNTs surface. Length of ZFNTs cannot be measured due to non-aligned ZFNT arrays. The effect of annealing temperature on morphology, crystal structure, surface properties, and optical properties of the nanotubes also were examined and correlated to photoreduction of Cr(VI). From the results, the amorphous FSZNTs with BET surface area 25.3 m2/g were more photoactive than the crystalline FSZNTs under sunlight (95% vs. 30% after 5 h) that attributed to enhanced Cr(VI) adsorption and enhanced light absorption. In addition, the mixed oxide ZTNTs and ZFNTs exhibited higher Cr(VI) removal efficiency than pure oxide nanotubes like ZrO2 nanotubes (ZNTs), TiO2 nanotubes (TNTs), and α-Fe2O3 + Fe3O4 nanotubes (FNTs) grown on Zr, Ti, and Fe foils, respectively that ascribed to high Cr(VI) adsorption and enhanced charge carriers separation. ZTNTs annealed at 600 °C has higher Cr(VI) removal efficiency than the ZTNTs annealed at 400 °C (100% vs. 53% after 5 h) implies strong UV absorption of orthorhombic-ZrTiO4 phase. Similarly, the Cr(VI) removal efficiency of ZFNTs annealed at 600 °C slightly higher than ZFNTs annealed at 400 °C (86% vs. 83% after 3 h) due to higher concentration of visible light active α-Fe2O3 phase. Among all samples, the mixed oxide ZFNTs were considered as the best photocatalyst due to excellent Cr(VI) adsorption and high photoactivity under sunlight.